Factores psicosociales que inciden en el intento de suicidio en niños/as de la cultura shuar de la escuela “andrès avelino jaramillo” de la ciudad de macas, periodo septiembre 2011 – marzo 2012. - Natali Marisol, Conde Centeno (2013)
This research work provides psychosocial factors in the categories; family as neglect, family dysfunction and abuse, while social factors such as poverty and psychological factors such as depression, affecting suicide attempts in children / as Shuar culture of the school "Andrés Avelino Jaramillo" in the city of Macas, the Shuar culture, present but little known, involves such factors as their own in their culture, but the relationship with the culture of settlers makes the child Shuar factors evidencing as damaging to him and his family. The aim of this research is to raise skills to prevent suicide attempts in children / as and work family socio; thereby focusing on Systemic Family Therapy, using the descriptive research type-explanatory, no field design experimental study with a type of Transversal